Faktor Yang Mempengaruhi Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023) - Tita Setia Putri; Juita Sukraini; Nidia Anggreni Das (Politeknik Raflesia Press, 2026)
The research aims to determine the influence of Managerial Ownership (X1), Institutional Ownership (X2), Board of Independent Commissioners (X3), and Audit Committee (X4) on Company Value (Y) in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. The population in this study was 32 Manufacturing companies in the Food and Beverage sub-sector. Sampling used the Purposive Sampling technique so that a total sample 0f 96 samples was obtained. The data analysis technique used the Generalized Least Square (GLS) through E-views software version 12. The results of the study indicate that Managerial Ownership (X1) has a significant effect on Company Value (Y). This result is proven by the t-statistic value of |2.701| ≥ |-2.195| and the Sig. value of 0.008 < 0.05. Institutional Ownership (X2) has a significant effect on Firm Value (Y). This result is proven by the t-statistic value |2.005| ≥ |-2.195| and the Sig. value 0.047 < 0.05. Board of Independent Commissioners (X3) does not have a significant effect on Company Value (Y). This result is proven by the t-statistic value |-0.852| ≤ |-2.195| and the Sig. value 0.396 > 0.05. Audit Committee (X4) has a significant effect on Company Value (Y). This result is proven by the t-statistic value of |2.115| ≥ |-2.195| and the Sig. value of 0.037 < 0.05. Managerial Ownership (X1), Institutional Ownership (X2), Board of Independent Commissioners (X3) and Audit Committee (X4) have a significant effect simultaneously on Company Value (Y) as proven by the Sig. value of 0.032 < 0.05.